2021
DOI: 10.3389/fgene.2021.721022
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Genetic Diversity Estimation of a Promising Domestication Medicinal Motherwort Leonurus Cardiaca Based on Chloroplast Genome Resources

Abstract: Leonurus cardiaca has a long history of use in western herbal medicine and is applied for the treatment of gynaecological conditions, anxiety, and heart diseases. Because of its botanical relationship to the primary Chinese species, L. japonicus, and extensive medical indications that go beyond the traditional indications for the Chinese species, it is a promising medicinal resource. Therefore, the features of genetic diversity and variability in the species have been prioritized. To explore these issues, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 81 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Deterministic or stochastic forces, such as natural selection and genetic drift, increase genetic diversity at several levels of biological organization (individuals, populations, and species) ( Sun et al, 2021 ). Higher genetic diversity generally results in more adapted genotypes and is associated with greater evolutionary potential and resilience of species or populations ( Falk and Holsinger, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deterministic or stochastic forces, such as natural selection and genetic drift, increase genetic diversity at several levels of biological organization (individuals, populations, and species) ( Sun et al, 2021 ). Higher genetic diversity generally results in more adapted genotypes and is associated with greater evolutionary potential and resilience of species or populations ( Falk and Holsinger, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, extremely low sequence diversity was exhibited. Consequently, we found that cp genomes of T. mongolica were highly conserved, as observed in most land plants, such as Leonurus Cardiaca (Sun et al, 2021), Cercidiphyllum japonicum (Zhu et al, 2020). Among the six cp genomes of Zygophyllaceae, genome length, organization and gene content of T. mongolica were more similar to the cp genome of Z. xanthoxylon and Z. mucronatum than to the remaining three species, exhibiting the drastically reduced IRs, the loss of ndh gene family and one copy of rRNAs.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, extremely low sequence diversity was exhibited. Consequently, we found that cp genomes of T. mongolica were highly conserved, as observed in most land plants, such as Leonurus Cardiaca ( Sun et al, 2021 ), Cercidiphyllum japonicum ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 72%
“…As mentioned above, Coptis is a genus with enormous value in research and development. Genetic diversity defines the evolutionary potential and resilience of species ( Sun et al., 2021 ). Thus, it is crucially important to evaluate the genetic diversity of this genus.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of next-generation sequencing technologies, plastome genome sequences can be obtained more efficiently by directly sequencing total genomic DNA and de novo assembling whole plastid genomes ( Sun et al., 2021 ). Due to its stable structure, rare recombination, moderate evolution rate, and largely uniparental inheritance, plastomes have been extensively used to reveal the evolutionary dynamics, such as phylogeny, phylogeography, demographic history and species diversity estimation ( Aguirre Planter et al., 2020 ; Dong et al., 2021a ; Dong et al., 2021b ; Wang Y. et al., 2021 ; Wang Z. et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%